Home-based telemonitoring versus hospital admission in high risk pregnancies: a qualitative study on women's experiences - J. F. M. van den Heuvel; C. J. Teunis; A. Franx; N. M. T. H. Crombag; M. N. Bekker (BMC, 2020)
Abstract Background Hospital admission during pregnancy complications is considered to be an event of significant impact. Besides conventional in-clinic maternal and fetal monitoring, recent technologies enable home-based telemonitoring with self-measurements in high risk pregnancy. This study is part of a feasibility pilot to explore the usability and acceptability of telemonitoring and aims to gain insight in the experiences and preferences of high risk pregnant women concerning the novel strategy of telemonitoring, opposed to women who were hospitalized in pregnancy. Methods Using secured Facebook Groups, we conducted four online focus groups: two focus groups with women who were admitted during pregnancy (n = 11) and two with women who received home telemonitoring in the pilot phase (n = 11). The qualitative data were analyzed thematically. Results Four major themes emerged from both participant groups: [1] care experience, [2] emotions regarding pregnancy, [3] privacy and [4] impact on daily life. Different views were reported on all four themes, resulting in a direct comparison of experiences during hospitalization and telemonitoring. Most admitted patients reported a growing sense of boredom and anxiety during their clinical admission. Lack of privacy on ward was a great concern, as it affected their contact with hospital staff and family. This issue was not reported amongst telemonitored women. These participants still felt like a patient at times but responded that the comfort of their own home and bed was pleasant. Only a minority of telemonitored participants reported being anxious at times at home, while not having a physician or nurse nearby. Being at home resulted in less travel time for partners or family for hospital visits, which had its positive effects on family life. Conclusions Telemonitoring of a high-risk pregnancy provides an innovative manner to monitor fetal and maternal condition from home. Compared to the experiences of hospital admission in high risk pregnancy, it allows women to be in a comforting and private environment during an anxious time in their lives. As future studies should further investigate the safety and cost effectiveness of this novel strategy, women's views on the preference of telemonitoring need to be taken into consideration.